Study on Synthesis, Spectral Characterization and in vitro Antibacterial Evaluation of Triaza and Dioxa Aza Spiro Derivatives - Natarajan, Manivannan; Balachandravinayagam, Elanchezhian; Ganesan, Selvanathan; Selvaraju, Meenakshi (New Innovations in Chemistry and Biochemistry Vol. 2, 2021)
Six compounds 7,9-diphenyl-1,4-dioxa-8-azaspiro[4.5]decane 1-6 have been synthesized by Mannich reaction and cyclo condensation. The structures and stereochemistry established by Elemental analysis, Mass, IR, 1H,13C, NMR studies. The purities were checked by elemental analysis. The synthesized compounds 1-6 adopt chair conformation with equatorial orientation of the aryl groups by coupling constant values of 1H NMR. All the compounds were screened for their antibacterial activity against Proteus mirabilis, Klebsiella oxytoca, Staphylococcus aureus and Salmonella paratyphi. The compound 5 exhibited excellent in vitro antibacterial activity in all species.